119k views
0 votes
7m − 4 − 9m − 36 = 0

2 Answers

3 votes

Answer:

-20

Explanation:

7m − 4 − 9m − 36 = 0

-2m - 4 - 36 = 0

-2m - 40 = 0

-2m = 40

m = -20

User Mises
by
5.1k points
5 votes

Answer:

The answer is
m=-20

Explanation:

In order to determine the answer, we have to know about solving equations.

When we have to solve an equation of one variable, first we have to add similar terms. A term is just a variable with a coefficient. Similar terms have the same variable.

In this case, we have two terms:

  1. "m" variable.
  2. just a number.

Then we have to solve the variable "m". We have to free it in one side.

Adding similar terms:


7m-4-9m-36=0\\-2m-40=0\\-2m=40\\m=-(40)/(2)\\ \\m=-20

Finally, the answer is
m=-20

User Atul Verma
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.